Prenatal therapy in transient abnormal myelopoiesis: a systematic review. Issue 1 (8th May 2015) - Tamblyn, J A; Norton, A; Spurgeon, L; Donovan, V; Bedford Russell, A; Bonnici, J; Perkins, K; Vyas, P; Roberts, I; Kilby, M D
Abstract : Objective: To systematically review current evidence regarding prenatal diagnosis and management of transient abnormal myelopoiesis (TAM) in fetuses with trisomy 21. A novel case of GATA1 -positive TAM, in which following serial in utero blood transfusion clinical improvement and postnatal remission were observed, is included. Search strategy and data collection: A systematic search of electronic databases (inception to October 2014) and reference lists, hand-searching of journals and expert contact. All confirmed cases of prenatal TAM were included for analysis. Data on study characteristics, design and quality were obtained. Results: Of 73 potentially relevant citations identified, 22 studies were included, describing 39 fetuses. All studies included comprised single case or small cohort studies; overall quality was 'very low'. Fetal/neonatal outcome was poor; 12 stillbirths (30.8%), 4 neonatal deaths (10.2%) and 7 infant deaths (17.9%). In two cases, the pregnancy was terminated (5.1%). TAM was primarily detected in the third trimester (79.4%), and in 14 a retrospective diagnosis was made postpartum. Ultrasound features indicative of TAM included hepatomegaly±splenomegaly (79.5%), hydrops fetalis (30.8%), pericardial effusion (23.1%) and aberrant liquor volume (15.4%). When performed, liver function tests were abnormal in 91.6% of cases. Conclusions: Prenatal TAM presents a challenging diagnosis, and prognosis is poor, with consistently high mortality. A low threshold to measure haematological and biochemical markers is advised when clinical features typical of TAM are detected in the context of trisomy 21. Larger prospective studies are warranted to accurately ascertain the role of GATA1 analysis and potential value of prenatal therapy.